A proposito di Thomas H. Ogden e della psicoanalisi ontologica - Martini, Giuseppe (B@belonline, 2021)
Analysis of some central points of Ogden’s thought in generally considered of special relevance not only for psychoanalysts, but also for philosophers and, in particular, for a comparison between hermeneutics and psychoanalysis that takes into account the recent and radical transformations of this discipline both on a theoretical and clinical level.